Transcendence, historicity and temporality of being elderly: nursing reflection-using Heidegger - Raúl Fernando Guerrero-Castañeda; Marta Lenise do Prado; Silvana Silveira Kempfer; Maria Guadalupe Ojeda Vargas
ABSTRACT The objective is to reflect on historicity and temporality as paths for the transcendence of being elderly, based on the phenomenological concepts of Martin Heiddeger. A review of the concepts of transcendence, historicity and temporality was carried out in the work of Martín Heidegger, integrating them in the perspective of nursing for the elderly. The transcendence of the elderly adult is feasible by accessing the temporality of self in the path of its historicity to arrive at the understanding of itself that he has achieved: transcending, which is but a process of the Being itself. Being is time in itself existing in the world, existence given by the encounter of the past (to have been), present and future (becoming), the same encounter that determines the historicity of the Being. The encounter has been consummated and the Being is transcendence, with the understanding of the Being itself as a supreme point.